The Art of Software Innovation Eight Practice Areas to Inspire your Business - Pikkarainen, Minna; Codenie, Wim; Boucart, Nick; Heredia Alvaro, José Antonio (Springer Berlin Heidelberg : Imprint: Springer, 2011)
Imagine that you are the CEO of a software company. You know you compete in an environment that does not permit you to treat innovation as a secondary issue. But how should you manage your software innovation to get the most out of it? This book will provide you with the answer. Software innovation is multifaceted and the approaches used by companies can be very different. The team of authors that wrote this book took the assumption that there is no such thing as a universal software engineering process or innovation process. Some things work well for a certain company, others do not. The book is organized around what the authors call eight fundamental practice areas for innovation with software. Each practice area contains a number of activities that can help companies to master that practice area. It also contains industrial experience reports that illustrate the applicability of these practice areas in software companies and is structured in such a way that you can select and read only those practice areas that are relevant to your company. The book is written with an industrial target audience in mind. Its most important goal is to challenge companies by offering them a framework to become more innovation-driven, rather than engineering-driven. Intrigued? Here you will find details of what you and your company can do to understand, implement, and sustain continuous innovation.